Cylindroma with Stromal Adipose Tissue Metaplasia versus Arising in a Background of Nevus Lipomatosus. (16th March 2014) - Yu, Ryan; Alowami, Salem
Abstract : Nevus lipomatosus superficialis is a rare type of connective tissue nevus. Cylindroma is a benign skin appendage tumor with a predilection for the scalp of older females. We describe the case of a 56-year-old woman with a scalp lesion demonstrating histopathologic features consistent with benign cylindroma arising within a nevus lipomatosus superficialis. To our knowledge, this lesion has not been raised in the literature in the differential for cylindroma with what is presumed to be stromal adipose metaplasia.